Desirability of Outcome Ranking for the Management of Antimicrobial Therapy (DOOR MAT): A Framework for Assessing Antibiotic Selection Strategies in the Presence of Drug Resistance. (27th November 2020) - Wilson, Brigid M; Jiang, Yunyun; Jump, Robin L P; Viau, Roberto A; Perez, Federico; Bonomo, Robert A; Evans, Scott R
Abstract: The complexities of antibiotic resistance mean that successful stewardship must consider both the effectiveness of a given antibiotic and the spectrum of that therapy to minimize imposing further selective pressure. To meet this challenge, we propose the Desirability of Outcome Ranking approach for the Management of Antimicrobial Therapy (DOOR MAT), a flexible quantitative framework that evaluates the desirability of antibiotic selection. Herein, we describe the steps required to implement DOOR MAT and present examples to illustrate how the desirability of treatment selection can be evaluated using resistance information. While treatments and the scoring of treatment selections must be adapted to specific clinical settings, the principle of DOOR MAT remains constant: The most desirable antibiotic choice effectively treats the patient while exerting minimal pressure on future resistance. Abstract : To meet the challenges of antibiotic treatment and stewardship evaluation in the presence of antibiotic resistance, the Desirability of Outcome Ranking for the Management of Antimicrobial Therapy (DOOR MAT) offers a flexible quantitative framework that evaluates the desirability of antibiotic selection.